Management of nitrogen losses in co-composting of anaerobically digested faecal sludge with vegetable wastes - Marekia, Faith Muthoni; Thammarat Koottatep; Mulenga, Martin; Annachhatre, Ajit P.; Babel, Mukand Singh; Netherlands Fellowships Programmes (NFP); UNESCO-IHE-AIT (Pathum Thani, Thailand : Asian Institute of Technology, 2017)
This study aimed at investigating NH4+-N adsorptive capacity of coir pith (CP)/coconut powder in co-composting of anaerobically digested faecal sludge (FS), market vegetable waste (MW) and fallen dry leaves (DL). Adsorption of NH4+-N, meant reduced volatilization of NH3gas. Thus, to accomplish this, 3 specific objectives were set for this study. Firstly, to characterize the co-composting feedstocks. Secondly, to determine CP{u2019}s NH4+-N adsorptive capacity by setting up batch experiments. The last one was to set up co-composting mixes with varying CP. Most of the analytical procedures adopted for characterizing the afore mentioned feedstocks and compost, were heavily adopted from plant and soil methodologies. All the feedstocks yielded satisfactory characteristics of concern in co-composting process. These include moisture content, C/N ratio and pH. CP and DL were characterized as carbon rich sources having C/N ratios of 164.52 and 55.77. On the other hand, ADFS and VW portrayed nitrogen rich sources characteristics having C/N ratio of 8.67 and 8.99.Additionally, the feedstocks pH ranged at 5.5 to 7.65 which were all within the co-composting optimal pH. Furthermore, determination of CP{u2019}s NH4+-N adsorptive capacity was attained by setting up two batch adsorption experimental set ups . The studies were undertaken by varying initial NH4Cl solution concentrations, temperature i.e. (25.2, 30, 45 and 60)0C and pH (4, 7, 9 and 12). Afterwards, the derived CP adsorptive capacity data was fitted in both Langmuir and Freundlich Adsorption Models and the comparison between the two was tested at a confidence level of p<0.05 using regression analysis. The data fitting was more significant in Freundlich Isotherm Model as opposed to Langmuir. This indicated that CP{u2019}s adsorption mechanism was multilayer and not monolayer. However, at temperature 30 0C, pH 4 and 7; both Langmuir and Freundlich Isotherms were significant. Nevertheless CP adsorption seemed to increase with increase in both temperature and pH. This observation was attributed to its high buffering capacity due to presence of surface functional groups i.e. carboxylic and phenolic groups (Mussoloni., Paul, & Kannangara, 1999). However, this is not conclusive as further and several studies need to be undertaken to really make a conclusion. The last objective, was accomplished by setting up 4 experimental set ups in triplicates ie; Control, Set up 1, 2 and 3. In all the set ups, the volume ratios of ADFS: VW; DL was kept constant while the variable was CP. CP accounted for, 27.3%; 46.7% and 57.9 % of the total mix in Set up 1,2 and 3 respectively. Co-composting was done for a period of 60 days. The derived compost had the following Total nitrogen (TN); Control, 2.63%; Set up 1, 2.29%;Set up 2, 2.35% and Set up 3 had 2.17%. For Control and Set up 1, the initial TN losses were 13.4% and 21.54% while Set up 2 and 3 had gains of 16.08% and 21.34% compared to initial TN. The losses in Control and Set up could be attributed to their below 20 C/N ratio of 14.72 and 16.06 respectively. However, Set up 2 and 3 were 26.98 and 33.63 respectively. Additionally, the other likely attribution of the gain in Set up 2 and 3 could be the presence of CP. However, further studies need to be undertaken in understanding CP structural properties in relation to its potential use as an adsorbent and interaction with varying pH and temperatures.
A thesis submitted in partial fulfillment of the requirements for the Degree of Master of Science in Urban Water Engineering and Management jointly offered by the Asian Institute of Technology, Thailand and UNESCO-IHE, The Netherlands
Thesis (M.Sc.) - Asian Institute of Technology - UNESCO-IHE, 2017
Keywords: Sewage sludge -- Management; Sewage -- Purification -- Nitrogen removal